A survey of drug liking and cravings in patients using sublingual or intranasal ketamine for treatment resistant depression: A preliminary evaluation of real world addictive potential - Chubbs, Brittany; Wang, Jay; Archer, Shaina; Chrenek, Carson; Khullar, Atul; Wolowyk, Michael; Swainson, Jennifer (Frontiers in Psychiatry, 2022)
Ketamine has gained rapid popularity as a treatment option for treatment resistant depression (TRD). Though seen only in limited contexts, ketamine is a potential drug of abuse, addiction and diversion. Clinical ketamine studies to date have not systematically evaluated factors relevant to addiction risk in patients with TRD, but in treating patients with ketamine, risks of potential harms related to addiction must be considered. As clinical access to intravenous ketamine programs is limited in much of Canada, these considerations become even more important for clinicians who elect to offer patients less supervised, non-parenteral forms of ketamine treatment. This study explores factors relevant to addiction risk in a real-world sample of 33 patients with TRD currently or previously treated with sublingual (SL) or intranasal (IN) ketamine in the community. First, patients were surveyed using a Drug Liking and Craving Questionnaire (DLCQ) to assess their level of drug liking and craving for ketamine, and to screen for symptoms of a ketamine use disorder. Second, the pharmacy records of these patients were reviewed for red flags for addiction such as dose escalation or early refills. Third, surveys were administered to the treating psychiatrists of patients who had discontinued ketamine to determine if abuse concerns contributed to reason for discontinuation. Though limited to a small sample, results indicate that ketamine is not a universally liked or craved substance in patients with TRD. Prescribers of non-parenteral ketamine should monitor patients and prescribe cautiously. Factors related to addiction (as in the DLCQ) should be explored for clinicians to consider individual risk/benefit for judicious use of ketamine in patients with TRD.